Proses Komunikasi Persuasif Orangtua kepada Anak dalam Pengambilan Keputusan Terkait Pernikahan Dini - Yeshinta Seli Octavia; Winda Hardyanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research is motivated by the researcher's interest in the phenomenon of early marriage that occurs in Tuban Regency which occupies a high number of early marriages, namely the top 10 at the provincial level of East Java. In making decisions related to early marriage, the contribution of parents is quite large. Parents play a role in persuading children in various ways and backgrounds. The phenomenon was then researched using a qualitative approach with a case study method. The results of the study stated that the persuasive communication process of parents and children in decision-making was based on parents' excessive fear of promiscuity. In sending messages, the way to do it is to instill the view that early marriage is a good thing. Furthermore, the communicator learns the message so that in the change of attitude the child initially feels doubtful. Finally, with the involvement of other families, they turned doubts into volition. The process of persuasive communication with the use of affirmative messages is the way chosen by message communicators with the aim that children can accept the principle of early marriage.